Say that again: Quantifying patterns of production for children with autism using recurrence analysis - Mankovich, Amanda; Blume, Jessica; Wittke, Kacie; Mastergeorge, Ann M.; Paxton, Alexandra; Naigles, Letitia R. (Frontiers in Psychology, 2022)
The current research study characterized syntactic productivity across a range of 5-year-old children with autism and explored the degree to which this productivity was associated with standardized measures of language and autism symptomatology. Natural language samples were transcribed from play-based interactions between a clinician and participants with an autism diagnosis. Speech samples were parsed for grammatical morphemes and were used to generate measures of MLU and total number of utterances. We applied categorical recurrence quantification analysis, a technique used to quantify patterns of repetition in behaviors, to the children’s noun-related and verb-related speech. Recurrence metrics captured the degree to which children repeated specific lexical/grammatical units (i.e., recurrence rate) and the degree to which children repeated combinations of lexical/grammatical units (i.e., percent determinism). Findings indicated that beyond capturing patterns shown in traditional linguistic analysis, recurrence can reveal differences in the speech productions of children with autism spectrum disorder at the lexical and grammatical levels. We also found that the degree of repeating noun-related units and grammatical units was related to MLU and ADOS Severity Score, while the degree of repeating unit combinations (e.g., saying “the big fluffy dog” or the determiner-adjective-adjective-noun construction multiple times) in general was only related to MLU.